Analisa Prediksi Farmakokinetik Dan Toksisitas Efek Antikanker Payudara Pada Temulawak (Curcuma Zanthorrhiza) Secara In Silico - Errol Rakhmad Noordam (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Cancer is the main cause of death in developing countries. In Indonesia, breast cancer patients rank the most and are the first cause of death from cancer. Cancer treatment is carried out by surgery or by capturing cancer tissue which is then followed by chemotherapy but this can kill normal cells. Curcumin is the largest content in Temulawak (Curcuma zanthorrhiza). The results of docking using molegro virtual docker show that there is a protein bond with the Curcumin ligand, using a form of validation using various functional evaluations available in Sybil2, so it can be said that the docking value of Curcumin can show its anti-breast cancer effect activity.